Free-end saddle length influence on stress level in unilateral complex partial denture abutment teeth and retention elements - Patrnogić Vesna; Todorović Aleksandar; Šćepanović Miodrag; Radović Katarina; Vesnić Jelena; Grbović Aleksandar (Vojnosanitetski Pregled)
Background/Aim. Different types of dental restorations are used for the therapy of unilateral free-end saddle edentulism. Unilateral complex partial denture is one of the indications for the Kennedy class II partial edentulism. The abscence of major connector and denture plate is an advantage compared to the conventional restorations, because of better comfort and shorter period of adaptation. The aim of the study was to analyse the influence of free-end saddle length change on the behaviour of unilateral complex partial denture supporting structures. Methods. Stress levels of the canine and the first premolar as retentional teeth and the attachments were tested under the influence of physiological forces with the loading point shifting distally in relation to the saddle length change. A virtual real size 3D model of the fixed part of the restoration (the canine and the first premolar with milled crowns) was created using the CATIA computer program. It was connected to the mobile part of partial denture with the SD snap in latch attachment. Mobile part of the restoration was designed in the region of 2, 3 and 4 lateral teeth (second premolar, first, second and third molar). By using the finite element method (FEM) stress levels analysis was performed under the load of physiological forces of 150 N in the free-end saddle teeth zone. Results. The results of analysis show that physiological forces cause a different stress distribution on the abutment teeth and the attachment, depending on the saddle length. Conclusion. The stress level values obtained for the abutment teeth as well as the attachment are far lower than the marginal ones. The behaviour of the system changes under this defined stress, but no plastic deformation occurs.